2013
DOI: 10.1080/08870446.2012.737466
|View full text |Cite
|
Sign up to set email alerts
|

Embodying sexual subjectivity after cancer: A qualitative study of people with cancer and intimate partners

Abstract: Research has increasingly recognised the profound impact that cancer can have upon embodied subjectivity. However, there has been little acknowledgement of the centrality of sexuality to subjectivity, and marginalisation of the experiences of intimate partners of people with cancer. This Australian qualitative study explores the post-cancer experiences of embodied sexual subjectivity for 44 people with cancer (23 women and 21 men) and 35 partners of people with cancer (18 women and 17 men) across a range of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 58 publications
1
33
0
3
Order By: Relevance
“…It has previously been reported that women do not consider changes in sexual desire in their male partner with prostate cancer a major concern, as their primary focus is survival of their husband [126]. However, qualitative reports in the present study suggested that sexual changes were problematic for many women partners, as was also the case for male partners [111,112,129]. This suggests that the sexual concerns of partners, as well as those of people with cancer, should be part of the agenda of health professionals working in cancer care [82,83].…”
Section: Discussionmentioning
confidence: 50%
“…It has previously been reported that women do not consider changes in sexual desire in their male partner with prostate cancer a major concern, as their primary focus is survival of their husband [126]. However, qualitative reports in the present study suggested that sexual changes were problematic for many women partners, as was also the case for male partners [111,112,129]. This suggests that the sexual concerns of partners, as well as those of people with cancer, should be part of the agenda of health professionals working in cancer care [82,83].…”
Section: Discussionmentioning
confidence: 50%
“…These mutual barriers often result in an unfortunate stalemate in the consulting room, leading to unmet patient needs. Over and beyond the unmet need for communication about sexual health after cancer, survivors also perceive a loss of self-efficacy and confidence regarding how to address their sexual dysfunction [16]. When clinicians and patients do not communicate about sexual health after cancer, these perceptions may be reinforced and patients may wrongly conclude that little or nothing can be done to manage the sexual side effects of cancer and cancer treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Posttraumatic psychological factors also likely contribute to sexual dysfunction. Research on sexual activity in patients with other medical conditions such as cancer 18 and pelvic floor disruption 19,20 cite stress, anxiety, and depression as major contributors to sexual dysfunction. Similarly, the psychological and (Table 3).…”
Section: Discussionmentioning
confidence: 99%